Artifacts exploration of the Sumenep great mosque through ethnomathematics for mathematics and social learning - Firdiansyah, Adin Lazuardy; Fausi, Moh; Hidayati, Ariani Laili (Indonesian Journal of Science and Mathematics Education, 2024)
Ethnomathematics research is a part of qualitative research that uses the ethnographic method. This study aims to explore, describe, and interpret the patterns, values, and beliefs found in the artifacts and ornaments of the Great Mosque of Sumenep. The researcher is the primary instrument in data collection through interviews, observations, and documentation. Informants are selected using purposive sampling. Data validation is carried out using triangulation methods to be analyzed using descriptive analysis techniques. The study results indicate that these artifacts can be used as objects for learning mathematics and socio-cultural subjects. Students in their surroundings frequently encounter these objects. This research implies a student-centered learning approach based on ethnomathematics, where they are encouraged to explore the mosque's artifacts.Thus fostering a sense of ownership and meaning in the learning process.